GNAO1 organizes the cytoskeletal remodeling and firing of developing neurons. Issue 12 (27th October 2020) - Akamine, Satoshi; Okuzono, Sayaka; Yamamoto, Hiroyuki; Setoyama, Daiki; Sagata, Noriaki; Ohgidani, Masahiro; Kato, Takahiro A.; Ishitani, Tohru; Kato, Hiroki; Masuda, Keiji; Matsushita, Yuki; Ono, Hiroaki; et al.
Abstract: Developmental and epileptic encephalopathy (DEE) represents a group of neurodevelopmental disorders characterized by infantile‐onset intractable seizures and unfavorable prognosis of psychomotor development. To date, hundreds of genes have been linked to the onset of DEE. GNAO1 is a DEE‐associated gene encoding the alpha‐O1 subunit of guanine nucleotide‐binding protein (GαO ). Despite the increasing number of reported children with GNAO1 encephalopathy, the molecular mechanisms underlying their neurodevelopmental phenotypes remain elusive. We herein present that co‐immunoprecipitation and mass spectrometry analyses identified another DEE‐associated protein, SPTAN1, as an interacting partner of GαO . Silencing of endogenous Gnao1 attenuated the neurite outgrowth and calcium‐dependent signaling. Inactivation of GNAO1 in human‐induced pluripotent stem cells gave rise to anomalous brain organoids that only weakly expressed SPTAN1 and Ankyrin‐G. Furthermore, GNAO1 ‐deficient organoids failed to conduct synchronized firing to adjacent neurons. These data indicate that GαO and other DEE‐associated proteins organize the cytoskeletal remodeling and functional polarity of neurons in the developing brain.